The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/feduc.2017.00018
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the AAOS International Scholars Program after 14 Years: Professional Development and Education of the Recipients

Abstract: introduction: The AAOS International Scholars Program was launched in 2002 with the goal of enhancing the knowledge and skills of orthopedic surgeons in underserved regions. The goals of this study were to (1) characterize the professional and practice profile of scholarship recipients, (2) assess the perceived impact of this short-term educational experience on their clinical practice, (3) if/how the knowledge and skills have been disseminated to students and/or colleagues, and (4) assess career development i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Currently, many North American (NA) academic centers and professional societies provide such teaching and training opportunities for international surgeons (ISs) from LMICs. [6][7][8] A recent webbased search found that orthopaedic trauma was one of the most prevalent subspecialties among orthopaedic observerships available in North America to ISs. [12] However, the perceived impact of trauma-focused observerships on the visiting LMIC surgeons in the context of their own clinical practice has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many North American (NA) academic centers and professional societies provide such teaching and training opportunities for international surgeons (ISs) from LMICs. [6][7][8] A recent webbased search found that orthopaedic trauma was one of the most prevalent subspecialties among orthopaedic observerships available in North America to ISs. [12] However, the perceived impact of trauma-focused observerships on the visiting LMIC surgeons in the context of their own clinical practice has not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] The need for improving access to quality surgical care in medically underserved regions globally is well known to the orthopaedic community. [5–11]…”
Section: Introductionmentioning
confidence: 99%
“…Global surgical education has evolved from shortterm medical missions in LICs and MICs to the development of sustainable partnerships that allow for mutual learning opportunities and the creation of funding and career paths that foster collective responsibility in addressing global inequities in surgical care 2 . The need for improving surgical care in LICs and MICs is well known to the orthopaedic community [4][5][6][7][8][9][10][11] .…”
mentioning
confidence: 99%
“…Currently, many North American (NA) academic centers and professional societies provide international surgeons (ISs) short-term opportunities for clinical observerships 5,7 . In an attempt to better understand the impact of such clinical observerships on ISs and their home countries, a recent study found that participation in an NA pediatric orthopaedic observership had a positive perceived impact on the majority of visiting ISs, did not contribute to substantial brain drain, and may assist with local capacity-building 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation